High-fat diet impairs the dendritic morphology of hippocampal CA1 pyramidal neurons in male but not female mice - Teng, Shu-Fang; Lee, Ming Tatt; Lee, Li-Jen; Hwang, Ling-Ling; Chen, Ching-Ping; Lee, Hsin-Jung; Chen, Chiung-Tong; Chiou, Lih-Chu (Frontiers in Nutrition, 2025)
BackgroundObesity is associated with cognitive function impairment. We previously found that male, but not female, mice have poorer performance in learning and memory tasks and impaired hippocampal synaptic plasticity after long-term high-fat diet (HFD) consumption, compared to regular chow-fed counterparts. To elucidate the potential morphological mechanism(s), here we further performed morphometric analysis of hippocampal dendritic morphology and complexity in HFD and control groups of both sexes.MethodsC57BL/6 J mice with both sexes were fed HFD (45% kcal% fat) after weaning for 12 months. Age-matched control mice were fed regular chows (13.5 kcal% fat). Morphometric analysis of Golgi-stained dendrites in hippocampal slices was performed to compare the dendritic morphology and complexity of CA1 pyramidal neurons between HFD and control groups in male and female mice.ResultsCompared with the control group, HFD-fed male mice showed lower dendritic spine density in both apical and basal dendrites, and lesser dendritic complexity in basal dendrites, which was indicated by fewer bifurcation nodes, terminal endings and dendritic segments, and shorter total dendritic length. However, in female mice, HFD did not affect dendritic spine density and induced subtle changes in dendritic complexity. Nevertheless, in control groups, male mice inherently had higher dendritic spine density and more dendritic complexity than females.ConclusionThe present study provides the structural evidence, including the reduction of dendritic complexity and spine density, for HFD-induced male-specific functional impairments in hippocampal synaptic plasticity and memory performance.